Pemanfaatan Buah Naga Merah (Hylocereus polyrhizus) Sebagai Pewarna Alami dan Sumber Antioksidan Pada Bolu Kukus - Regilia, Dety; Darmawan, Eman; masrukan; Laswati, Dyah Titin (Universitas Widya Mataram, 2024)
The use of red dragon fruit as a natural dye has the potential to be developed as a source of antioxidants. This research aimed to determine the effect of the ratio of red dragon fruit on the chemical, physical and organoleptic properties of steamed sponge cake. This research used a randomized block design (RAK), with one factor: adding red dragon fruit, which consisted of 5 treatments. Each treatment was subjected to chemical testing (water content, ash, fat, protein, carbohydrate and antioxidant activity) and physical and organoleptic tests. The test data were analyzed using the ANOVA statistical test. If there were differences, a follow-up test was conducted with DMRT with a significance level (α=0.05%). Based on the results of this research, it can be concluded that The addition of red dragon fruit has a significant effect on increasing water content, ash, and antioxidant activity, but has no effect on fat, protein and carbohydrate levels. Dragon fruit steamed sponge cake that is acceptable/preferred (3.76) is a steamed sponge cake with a red dragon fruit ratio of 36 g, pink colour (3.36), very soft texture (4.2), no dragon fruit taste (4 .0), no dragon fruit aroma (4.1), water content 7.78%, ash content 7.39% db, fat content 3.15% db, protein content 10.32% db, carbohydrate content 78, 45 5 db, and antioxidant activity levels of 19.39%.